A Sociolinguistic Approach to Teaching Spanish Grammatical Structures. (17th February 2017) - Shin, Naomi L.; Hudgens Henderson, Mary
Abstract: Advanced grammar courses often present standardized grammar rules to students without considering sociolinguistic variation. As a result, many native/heritage students feel that they speak "incorrectly, " and many second language learners do not get an accurate picture of the target language's real‐world grammar. This article describes and evaluates a unique approach to teaching advanced Spanish grammar to university students. The curriculum focuses on core grammatical content by studying structures that are subject to sociolinguistic variation, as in había ∼ habían dos ranas [there was ∼ were two frogs], and it highlights the sociopolitical factors that explain why some forms are deemed prestigious. To test the efficacy of this curriculum, students enrolled in an advanced Spanish grammar course at a large university in the southwestern United States completed a pre‐ and posttest that measured Spanish grammar knowledge, awareness of sociolinguistic concepts, and positive language attitudes. Results showed statistically significant gains with respect to knowledge of grammar and sociolinguistics. Students also demonstrated a heightened awareness of how prejudice can manifest in judgments of spoken language.